Dynamic Windage Yaw Angle and Dynamic Wind Load Factor of a Suspension Insulator String. (16th February 2022) - Zhao, Shuang; Yue, Jiahao; Savory, Eric; Yan, Zhitao; Chen, Jiahao; Zhang, Bin; Peng, Liuliu
Abstract : A simplified calculation method is proposed for determining the peak dynamic windage yaw angle φ ^ of electricity transmission line (TL) tower suspension insulator strings (SISs). According to the rigid-body rule, the geometric stiffness matrix in the calculation of the windage yaw angle φ of SISs is dominated by the average wind loads, while the fluctuating wind loads are the dominant factor in the elastic stiffness. With the average wind state of conductors as the initial calculation condition, the load-response-correlation (LRC) method can be used to determine the fluctuating windage yaw angle φ d and the corresponding equivalent static wind loads (ESWLs). Then, the improved rigid straight rod model, which uses the actual length of conductors rather than the projected length, was used to determine the average windage yaw angle φ ¯ . Through the linear superposition of the horizontal increments of φ ¯ and φ ^ d (the peak value of φ d ), the formulae to calculate the φ ^ of SISs were derived. Additionally, the formulae for the dynamic wind load factor, β c, which is a key factor in designing wind loads for φ, were derived according to the principle of ESWLs, rather than being empirically determined by the Chinese code. Thus, the calculation model regarding the loads and response for the φ of SISs was established, and an actual TL was used to verify the established calculation model. Afterward, the influence of the different engineering design parameters on φ and its β c were analyzed. The parameter analyses show that the wind speed, span, and ground roughness influence the magnitudes of φ ^ and β c, however, the height difference between the two suspension points of the conductors, the nominal height, and the sag-to-span ratio may be neglected in the approximate calculation. Our method offers a new solution to TL design when there are large deformations and small strains.